2021
DOI: 10.3390/coatings11101201
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the Adhesive Contact Behaviors between a Viscoelastic Stamp and a Transferred Element in Microtransfer Printing

Abstract: Microtransfer printing is a sophisticated technique for the heterogeneous integration of separately fabricated micro/nano-elements into functional systems by virtue of an elastomeric stamp. One important factor influencing the capability of this technique depends on the adhesion between the viscoelastic stamp and the transferred element. To provide theoretical guidance for the control of adhesion in the transfer printing process, a finite element model for the viscoelastic adhesive contact between a polydimeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…In addition, Van Dokkum et al [18] observed, in a similar problem, the normalized effective surface energy Δ ef f ∕Δ (or equivalently FPO ) decreases with the Tabor parameter. Furthermore, Jiang et al [19], performing FE calculations on the pull-off force of a spherical indenter from a soft viscoelastic stamp, observed a reduction of FPO when decreasing Δγ . Similarly to our approach, they changed the value of Δγ maintaining the same maximum penetration max .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Van Dokkum et al [18] observed, in a similar problem, the normalized effective surface energy Δ ef f ∕Δ (or equivalently FPO ) decreases with the Tabor parameter. Furthermore, Jiang et al [19], performing FE calculations on the pull-off force of a spherical indenter from a soft viscoelastic stamp, observed a reduction of FPO when decreasing Δγ . Similarly to our approach, they changed the value of Δγ maintaining the same maximum penetration max .…”
Section: Resultsmentioning
confidence: 99%
“…In such case, the substrate is in a fully relaxed state at the end of the loading phase. Notice the same condition can be reached by loading at nonzero velocity and waiting a sufficient long dwell time (t 0 → ∞) before unloading [11,19]. If unloading is then performed at nonzero V , the maximum pull-off force F PO(max) , which is asymptotically reached at high contact line velocities V c = −da/dt [9], should be…”
Section: Unloading From Relaxed Statementioning
confidence: 81%
“…In a recent work, Jiang et al [19] developed a finite element model for the viscoelastic adhesive contact between a PDMS stamp and a sphere. In their simulations, unloading starts from a relaxed state of the viscoelastic stamp.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Jiang et al [17], performing FE calculations on the pull-off force of a spherical indenter from a soft viscoelastic stamp, observed a reduction of FPO when decreasing ∆γ.…”
Section: Resultsmentioning
confidence: 99%